Bioremediation of Spent Bleaching Earth (SBE) Waste Using Lipolytic Fungi - Riezkatama Menangcaye; Adipati Napoleon; Bambang Yudono (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2018)
The purpose of this research was to obtain the effectiveness level of bioremediation process of oil residue on SBE waste by using the isolates of lipolytic fungus Aspergilus fumigatus, Cylindrocladium sp and Fumago sp. This research was conducted by using completely randomized factorial design with 3 factors of treatment which consist of nutrient ratio (N:P:K) that were divided into three levels, namely n1=A(7:1.5:0.5), n2=B(14:3:1), n3=C(21:6:1.5). The humidity were divided into 3 levels treatment i.e. k1 (90%), k2 (80%), k3 (70%) and time that were divided into four levels, namely w1 (week 1), w2 (week 2), w3 (week 3), and w4 (week 4) with fixed pH i.e. pH 6, so that were obtained 36 combination of treatment and for each treatment combination repeated 3 times. Sampling of SBE waste was conducted in one cooking oil factory in South Sumatera using randomized sampling method as much as 24.000 g. The results showed that 80% humidity and nutrient A as the best treatment for lipolytic fungus consortium performance to degrade the SBE waste with the average percentage of oil degradation as much as 74.83%. 80% humidity and nutrient A was an effective interaction in affecting the percentage of oil degradation.